TINJAUAN TEOLOGIS KONSEP BANGSA ISRAEL TENTANG KEMATIAN - David Susilo Pranoto (Manna Rafflesia, 2017)
The concept of death is something that is often questioned by humans. Because no human being has been able to provide strong evidence of what happened after death. Therefore this question also needs to be answered in the light of the Christian faith. The rationale for discussing death is the Bible. But it must be realized that the Bible is also present in the cultural context and traditions of the nation of Israel. So to get the principle or meaning needed is also an assessment of the context and principle of death of the people of Israel. Theological review is needed so as not to get caught up in Judaism in understanding the concept of death. Therefore, through this paper will explain the theological review of the concept of the nation of Israel about death.